Analysis of the Effectiveness of Quizizz and Kahoot Gamification Learning Media on Improving Students' Conceptual Understanding: An Empirical Study at STKIP Budidaya Binjai - Poppy Hasnah Harahap; Pane, Sri Hartati; Susanty Siregar, Susi; Irhami Tanjung, Syahri; Beru Ginting, Sri Ulina; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence (IJERE), 2026)
The transformation of digital era learning necessitates the adoption of educational technology that is responsive to the cognitive characteristics of contemporary students. This study explores the comparative effectiveness of the Quizizz and Kahoot gamification platforms in improving the conceptual understanding of STKIP Budidaya Binjai students. Using a quasi- experimental design with a pretest-posttest control group involving ninety (n=90) students distributed into three groups: experimental group 1 (Quizizz, n=30), experimental group 2 (Kahoot, n=30), and a control group (conventional method, n=30). The learning intervention was implemented for eight weeks in the Indonesian Language Learning Strategy course. Data collection instruments included a conceptual understanding test, an academic engagement questionnaire, and participant observation. Significant findings indicated that the Quizizz group showed a 34.7% increase in mean scores (from 62.3 to 84.0), the Kahoot group increased by 28.5% (from 61.8 to 79.4), while the control group only increased by 12.3% (from 63.1 to 70.9). Academic engagement showed that 87.3% of students in the Quizizz group and 83.7% in the Kahoot group reported high motivation compared to 54.2% in the control group. The distinguishing characteristics of the two platforms—self-paced, self-paced learning on Quizizz versus real-time competitive learning on Kahoot—resulted in different learning outcome profiles: Quizizz excelled in deep understanding and long-term retention, while Kahoot excelled in immediate recall and class enthusiasm. The study recommends strategic integration of the two platforms based on specific learning objectives and pedagogical contexts. Implications of the study indicate the need for institutional support in technological infrastructure and faculty professional development to optimize gamification-based learning